2019
DOI: 10.1111/cbdd.13615
|View full text |Cite
|
Sign up to set email alerts
|

A kojic acid derivative promotes intrinsic apoptotic pathway of hepatocellular carcinoma cells without incurring drug resistance

Abstract: Hepatocellular carcinoma is one of the most pervasive cancers with low prognosis, high frequency of recurrence, and metastasis. Studies conducted have focused on extricating novel strategies for successful treatment. Kojic acid and its derivatives are already proven to have depigmenting, anti‐inflammatory, and anti‐neoplastic properties. In the present study, kojic acid and its 10 distinct derivatives were tested on HEPG2 cell line for their possible anti‐cancer effect and seven of them were observed to be cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Non-cancerous cell lines, such as HGF-1 human gingival fibroblasts and MRC-5 human lung cell lines, can be employed. 16,17,68 The antitumor studies evaluated in this review demonstrated toxic effects of kojic acid derivatives for cancerous cell lines and safe concentrations for normal cell lines in cell viability assays with IC50 determinations, indicating the studied kojic acid derivatives as safe molecules in such conditions.…”
Section: Safe T Y Reg Ard Ing H Uman Us E Of Koj I C Acid and Derivat...mentioning
confidence: 78%
See 1 more Smart Citation
“…Non-cancerous cell lines, such as HGF-1 human gingival fibroblasts and MRC-5 human lung cell lines, can be employed. 16,17,68 The antitumor studies evaluated in this review demonstrated toxic effects of kojic acid derivatives for cancerous cell lines and safe concentrations for normal cell lines in cell viability assays with IC50 determinations, indicating the studied kojic acid derivatives as safe molecules in such conditions.…”
Section: Safe T Y Reg Ard Ing H Uman Us E Of Koj I C Acid and Derivat...mentioning
confidence: 78%
“…For HEPG2 hepatocellular carcinoma cell line, kojic acid derivatives trigger an intrinsic p53 apoptotic pathway by increasing intracellular ROS concentration. The derivatives led to mitochondrial events which caused activation of caspase 3/7, hence apoptosis 68. Antitumor activity of metal complexes of kojic acid was tested on VC-8-BRCA & VC-8, (ovarian cancer cell lines).…”
mentioning
confidence: 99%
“…carcinoma cells, and the use of the piperidine Mannich bases in investigating its mechanism of action showed that it triggered apoptosis by increasing the levels of intracellular ROS, induction of TP53 gene, and activation of caspase 3/7 [65] . In another series of Mannich bases of allomaltol, compound 51 (R =H, R 1 =3,4‐Cl 2 ) (Figure 7) was found to be the most potent against MCF‐7 cells (IC 50 = 97 μM) and also against MDA‐MB‐231 (IC 50 = 48 μM), and investigation of its mechanism of action demonstrated that apoptosis occurred predominantly either through a p53‐dependent or through a p53‐independent mechanism, depending of the type of breast cancer cell involved [66] .…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Derived F...mentioning
confidence: 99%
“…In a collection of ten bisaminomethyl derivatives of 3-hydroxypyran-4-one, two compounds 52 (R 1 = 2-F-4-Br, NR 2 = piperidin-1-yl or pyrrolidin-1-yl) (Figure 7) had IC 50 values of approximately 35 μM against HepG2 hepatocellular carcinoma cells, and the use of the piperidine Mannich bases in investigating its mechanism of action showed that it triggered apoptosis by increasing the levels of intracellular ROS, induction of TP53 gene, and activation of caspase 3/7. [65] In another series of Mannich bases of allomaltol, compound 51 (R = H, R 1 = 3,4-Cl 2 ) (Figure 7) was found to be the most potent against MCF-7 cells (IC 50 = 97 μM) and also against MDA-MB-231 (IC 50 = 48 μM), and investigation of its mechanism of action demonstrated that apoptosis occurred predominantly either through a p53-dependent or through a p53-independent mechanism, depending of the type of breast cancer cell involved. [66] The best IC 50 value of a Mannich base 53 (Figure 7) obtained from kojic acid as substrate and ciprofloxacin as amine reagent was against HCT-116 human hepatoma cell line (IC 50 = 88 μM), while the copper complex of compound 53 was more potent against HepG2 (IC 50 = 11 μM).…”
Section: Chemmedchemmentioning
confidence: 99%
“…1 5-Hydroxy-2-(hydroxymethyl)-4 H -pyran-4-one, commonly known as kojic acid is an oxygen-containing natural γ-pyrone generated by filamentous fungi and numerous kinds of bacteria including Aspergillus , Penicillium, and Acetobacter, etc. 2 The kojic acid nucleus and its analogs have drawn immense significance in recent years due to their various application in the medicinal and pharmaceutical industry, 3 food industry, 4 cosmetic and personal care products, 5 agriculture, 6 and chemical industry. 7 By taking into consideration kojic acid's structural characteristics and broad-spectrum activities, a substantial attempt was made not just towards its synthesis but also to using them as an essential constituent for construction and identification of potent structural fragments.…”
Section: Introductionmentioning
confidence: 99%